Assessing the Efficiency of Soya Bean Marketing In the Ejura-Sekyedumasi and Nkoranza South Districts of Ghana - E, Frimpong; E.A, Boamah; J.S, Dittoh; S.K, Gandhi; A.E; Owusu, Kusi; V (British Journal of Marketing Studies, 2016)
The study aimed at assessing the efficiencies of soya bean marketing channels in the Ejura-Sekyedumasi and Nkoranza South Districts, Ghana. The multi-stage sampling technique was employed in selecting thirty-seven soya bean farmers, two wholesalers, seven retailers, two small-scale processors and one large-scale processor of soya beans for the study. Gross Margin analysis was employed in determining the marketing costs and margins whereas the Shepherd’s Method was used in analyzing the efficiencies of the marketing channels. The study revealed that nine different channels existed through which soya bean was marketed in the study areas, with the simplest channel (Channel 1) being where farmers sell directly to consumers. Analysis of marketing cost and margins revealed that comparatively, Channel 1 had the least cost (GH?2.40) and margins (GH?10.50) since farmers dealt directly with consumers without any interference from market intermediaries, who usually increase transaction cost. From the study, Channel 1 was the most efficient channel with an Efficiency Index of 37.71. Thus, its marketing cost constituted a smaller proportion of the consumer price. The study recommends that farmers use Channel 1 where they sell directly to consumers to market their produce and also form co-operatives to protect them against price fluctuation and give them assurance of buyers. Moreso, the central government is directed to intervene in the form of road construction and improvement to help reduce the excessive transportation cost associated with the soya bean trade in Ghana